Microparticles (CD146) and Arterial Stiffness Versus Carotid Intima Media Thickness as an Early Predictors of Vascular Affection in Systemic Lupus Patients - Sahar NASSEF; Hala El GUINDEY; Mary FAWZY; Amal NASSER; Rasha REFFAI; Doa SHEMIY (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate cluster of differentiation 146 (CD146) and pulse wave velocity (PWV) as non-invasive methods for prediction of early vascular affection in systemic lupus erythematosus (SLE) patients without symptoms of vascular disease, to detect the outcome and reproducibility of these methods, and to correlate CD146 and PWV with lipid profile, intima media thickness (IMT), and ankle brachial index. Patients and methods: Thirty female SLE patients (mean age 26.6±6.6 years; range 15 to 35 years) fulfilling the American College of Rheumatology 1997 revised criteria for SLE classification, and 15 age and sex matched healthy controls were included. All participants were performed full clinical assessments including measurement of Systemic Lupus Erythematosus Disease Activity Index, lipid profile, CD146, carotid IMT, PWV, and rise time as an indication of how fast the waveform rises. Results: Cluster of differentiation 146 levels were elevated in patients with SLE compared to controls (p<0.001). There was a statistically significant difference between patients and controls in the femoral, lower thigh, and ankle rise time. There was a statistically significant correlation between IMT and ages of patients, Systemic Lupus Erythematosus Disease Activity Index, and brachial-below knee PWV, while there was no correlation between IMT and disease duration, lipid profile, brachial-femoral PWV, and brachial-ankle PWV. There was statistically significant correlations between brachial-femoral PWV and serum cholesterol level, and between brachial-ankle PWV and low density lipoprotein cholesterol. Conclusion: Our results showed that SLE vascular affection is more pronounced in small arteries. Also, elevated CD146 and brachial-femoral PWV are useful early markers of vascular affection in SLE as well as rise time may be a marker for arterial stiffness.